KARAKTERISTIK INOVASI PENDIDIKAN DI PERGUAN TINGGI KEAGAMAAN ISLAM - Munib, Abdul (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2016)
The development of education, as well as the world of Islamic education, it cannot be separated from the name of renewal or other term innovation to achieve a better direction, therefore, the activities of Innovation education in world Islamic education needs to be done and developed to solve problems exist and thrive in the world of education. Therefore, the existence of activities of educational innovation is a new idea, which is perceived as a novelty for individuals or groups of people who are competent in the field and the world of education, educational innovations that do it either result inversion or discoveri, designed and used for achieve an educational goal or solve problems in education. But in the context of education, innovation can be run properly and will generate a positive thing, and better, if education practitioners understand some of the characteristics of the educational innovation, because it is inherent in the nature of educational innovation itself. Various models can Invention Education Innovation, Development, Diffusion and others. While the characteristics of educational innovation can be a relative advantage, Compatibility, testability, observability, Complexity, and so forth.